2012
DOI: 10.1002/eco.1330
|View full text |Cite
|
Sign up to set email alerts
|

Six decades of changes in the riparian corridor of a Mediterranean river: a synthetic analysis based on historical data sources

Abstract: (2012). Six decades of changes in the riparian corridor of a Mediterranean river: A synthetic analysis based on historical data sources. Ecohydrology, 6 (4): 536¿553. doi:10.1002/eco.1330.1 This is a pre-copyedited, author-produced PDF version following peer review of the article: Garófano-Gómez, V., F. Martínez-Capel, W. Bertoldi, A. Gurnell, J. Estornell, F. Segura-Beltrán. 2013 ABSTRACTRiparian corridors in semi-arid Mediterranean environments are ecosystems of high biodiversity and complexity. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 121 publications
(124 reference statements)
0
38
0
1
Order By: Relevance
“…Many responses of riparian communities to regulation of flows and water levels have been identified world‐wide (Greet, Cousens, & Webb, ; Johnson & Waller, ; Nilsson & Berggren, ), including vegetation encroachment, interruptions of natural regeneration, senescence of forests, increasing stress and disease‐induced mortality, reduced growth rate, altered recruitment, failure of seedling establishment, longitudinal and lateral fragmentation (Belmar, Bruno, Martínez‐Capel, Barquín, & Velasco, ; Garófano‐Gómez et al., ; González, González‐Sanchís, Cabezas, Comín, & Muller, ; González, González‐Sanchis, Comín, & Muller, ), and shifts in the composition and diversity of riparian vegetation (Bejarano, Nilsson, González del Tánago, & Marchamalo, ; Rood, Braatne, & Goater, ; Webb et al., ). The responses to altered flows of the riparian ecosystems remain a long‐standing challenge in Mediterranean regions (Belmar et al., ; Dallas, ; Garófano‐Gómez et al., ), likely a result of the multiple external pressures that influence these ecosystems, either directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many responses of riparian communities to regulation of flows and water levels have been identified world‐wide (Greet, Cousens, & Webb, ; Johnson & Waller, ; Nilsson & Berggren, ), including vegetation encroachment, interruptions of natural regeneration, senescence of forests, increasing stress and disease‐induced mortality, reduced growth rate, altered recruitment, failure of seedling establishment, longitudinal and lateral fragmentation (Belmar, Bruno, Martínez‐Capel, Barquín, & Velasco, ; Garófano‐Gómez et al., ; González, González‐Sanchís, Cabezas, Comín, & Muller, ; González, González‐Sanchis, Comín, & Muller, ), and shifts in the composition and diversity of riparian vegetation (Bejarano, Nilsson, González del Tánago, & Marchamalo, ; Rood, Braatne, & Goater, ; Webb et al., ). The responses to altered flows of the riparian ecosystems remain a long‐standing challenge in Mediterranean regions (Belmar et al., ; Dallas, ; Garófano‐Gómez et al., ), likely a result of the multiple external pressures that influence these ecosystems, either directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the functioning of riparian ecosystems in hydropower rivers is still limited. Several studies have shed light on the spatio‐temporal changes in dammed rivers within the novel hydrogeomorphological environments (Aguiar, Martins, Silva, & Fernandes, ; Garófano‐Gómez et al., ; Gurnell, Bertoldi, & Corenblit, ), whereas others have shown the effects of water diversion on channel geometry and riparian plant community composition and diversity (Caskey et al., ). Besides the alteration of timing, quantity, quality and predictability of flows due to damming, riparian forests are stressed by intensive land use pressures, particularly in the Mediterranean Europe (Clerici, Paracchini, & Maes, ; Dufour, Rinaldi, Piégay, & Michalon, ; Santos, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methods for mapping and analysing channel changes have been widely developed and applied (Garófano-Gómez et al, 2013;Gurnell, 1997;Hooke, 1984;Hooke & Yorke, 2010). Likewise, vegetation changes have been studied both in riverine and other environments, many studies using satellite imagery (Bertoldi, Drake, & Gurnell, 2011) but many, especially on decadal timescales, have used aerial photographs, as here (Dixon & Johnson, 1999;Garófano-Gómez et al, 2013;Gonzalez, Gonzalez-Sanchis, Cabezas, Comin, & Muller, 2010;Kondolf, Piegay, & Landon, 2007;Lunt, Winsemius, McDonald, Morgan, & Dehaan, 2010;Yang & Tien, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, vegetation changes have been studied both in riverine and other environments, many studies using satellite imagery (Bertoldi, Drake, & Gurnell, 2011) but many, especially on decadal timescales, have used aerial photographs, as here (Dixon & Johnson, 1999;Garófano-Gómez et al, 2013;Gonzalez, Gonzalez-Sanchis, Cabezas, Comin, & Muller, 2010;Kondolf, Piegay, & Landon, 2007;Lunt, Winsemius, McDonald, Morgan, & Dehaan, 2010;Yang & Tien, 2010). Increases in woody riparian area have been found but many of the cases are associated with change in river regime (Dixon & Johnson, 1999;Johnson, 1994;Perona, Molnar, Savina, & Burlando, 2009), especially due to dam control (Dixon, Johnson, Scott, Bowen, & Rabbe, 2012;Gonzalez et al, 2010;Merritt & Cooper, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These vegetation communities were not yet present (or did not have adult form) in the 1994 aerial photograph but appeared clearly consolidated in the 2000 image, after a long period without floods (1993–2001) that could have favoured vegetation development at the flowing channel banks. In another river of the region affected by damming, the Mijares River, Garófano‐Gómez et al () observed a period of the same duration (40 years) between reservoir construction and the completion of the process of encroachment of dense woody vegetation, whereas Martínez‐Fernández et al () have identified a similar stage of stability between 2000 and 2015 in Northwestern Spain.…”
Section: Discussionmentioning
confidence: 99%